Raiding nature’s genetic toolbox for UV-C resistance by functional metagenomics - Garrett A. Roberts Kingman; Justin L. Kipness; Lynn J. Rothschild (Scientific Reports)
Abstract As we assess the habitability of other worlds, we are limited by being able to only study terrestrial life adapted to terrestrial conditions. The environments found on Earth, though tremendously diverse, do not approach the multitude of potentially habitable environments beyond Earth, and so limited terrestrial adaptive capabilities tell us little about the fundamental biochemical boundaries of life. One approach to this problem is to use experimental laboratory evolution to adapt microbes to these novel environmental conditions. This approach can be dramatically improved through functional metagenomics, large-scale introduction of foreign genetic material to screen for phenotypes in a new host organism. This takes advantage of Earth’s immense biological diversity with high-throughput screening for genetic tools that can facilitate adaptation. We address a key gap in functional metagenomics work by exploring the impact of the experimental parameters chosen for functional metagenomics libraries. Experimental design dictates both fragment size and copy number, and we show that both can have outsized effects on the resultant phenotypes in non-intuitive ways. These results highlight the potential of functional metagenomics for adapting life rapidly to challenging new environments, with important implications in both astrobiology and bioindustry, while also emphasizing the impacts of decisions in experimental design.